The perception of underprivileged groups towards the effectiveness of the poverty eradication programs monitered and sponsored by Pejabat Pembangunan Negeri Johor (PPNJ) / Haslenda Yusop, Prof Madya Ruhana Zainudin and Nor Hazreeni Hamzah - Yusop, Haslenda; Zainudin, Ruhana; Hamzah, Nor Hazreeni (Research Management Institute (RMI), 2013)
Eradicate extreme hunger and poverty was the first goal to be achieved in Millennium Development Goals (MDGs) in Malaysia. Starting in 1970s, Malaysia had started the development goal of eradicating poverty. In conjunction with to reach MDGs goal government of Malaysia had launched a lot of poverty eradication programs in every state in Malaysia. The purpose of this program was to reduce the number of poverty. Some organizations like ministries or department of Malaysia's government had involved in monitoring the programs such as Rural Ministry, State Development Office and so on. The examples of the poverty eradication programs are Program Bantuan Rakyat (PBR), Projek Peningkatan Pendapatan (PPP), Projek Champion, Program Pembangunan Modal Insan (PPMI), Peluang pekerjaan, Bantuan kewangan bilanan dan bantuan pendidikan. The problem of poverty force the government to construct and planning the appropriate strategy of poverty eradication programs, so that the contents of poverty eradication programs that will be launched are appropriate with the current environment.